Pengaruh Customer Relationship Management dan Kualitas Pelayanan terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah di PT Bank Central Asia - Izhar Ismail Dano Dasim; Chatarina Yunita Tarigan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of the research is to identify whether Customer Relationship Management and Service Quality influence Customer Loyalty through Customer Satisfaction at PT Bank Central Asia. A total of 185 respondents were collected, and the technique used was purposive sampling using the SmartPLS 3.0 program. In this research, the methodology used is quantitative and descriptive. The population of this research is customers who make transactions at PT Bank Central Asia. The results of this research identify that Customer Relationship Management has a significant effect on Customer Satisfaction, Customer Relaitonship Management has a significant effect on Customer Loyalty, Customer Satisfaction has a significant effect on Customer Loyalty, Service Quality has a significant effect on Customer Satisfaction, Service Quality has a significant effect on Customer Loyalty, Customer Relationship Management has a significant influence on Customer Loyalty through Customer Satisfaction and Service Quality has a significant influence on Customer Loyalty through Customer Satisfaction.